The Burden of Depressive and Anxiety Disorders in Nepal, 1990-2017: An Analysis of Global Burden of Disease Data - Bhatta , Deepa Kumari; Budhathoki , Kreeti; Paudel, Kiran; Paudel, Shishir; Marhatta, Sujan Babu; Mahat , Smritee; Banskota, Avinaya; Joshi, Yadav Prasad (Journal of Karnali Academy of Health Sciences, 2022)
Background: Depressive disorders are frequent mental disorders that rank as top contributors of disability worldwide. Despite their burgeoning concerns, these are still one of the unheeded issues in developing nations. This study aims to describe the burden of major mental health disorders in Nepal in terms of Year Lived with Disability and Disability-Adjusted Life Year by age and sex standardization. Methods: The publicly available Global Burden of Disease (GBD) data from 1990 to 2017 was used for this study. The age and sex-specific incidence, prevalence rate, YLDs, and DALYs were examined among 100,000populations.Results: It was noted that females had the higher prevalence of depressive [4094.4 (95% uncertainty interval [UI]: 3761.9-4470.3 per 100,000 100,000)] and anxiety [4496.8 (95% UI: 4171.9-4837.9 per 100,000 100,000)] disorders. The prevalence of major depressive disorders was comparatively higher in females (2766.7) than males (1822.9). Females also had higher YLDs for both depressive and anxiety disorders. In 2017, higher DALYs of anxiety disorder were found in the females of 45-49 years (630.1). Childhood sexual abuse was found to be the major risk factor for depressive disorder, contributing to 32.5 DALYs in both sexes. Bullying, victimization had contributed to 26.7 DALYs of anxiety.Conclusion: There is a high burden of mental disorders in females of Nepal. This finding would support in identifying major mental health challenges of the country and in developing plans and interventions based on preventive, curative, and rehabilitative strategies.